Doubly bridged anthracenes: blue emitters for OLEDs [data] - Ludwig, Philipp; Mayer, Jacob; Ahrens, Lukas; Rominger, Frank; Ligorio, Giovanni; Hermerschmidt, Felix; List-Kratochvil, Emil; Freudenberg, Jan; Bunz, Uwe H. F. (Universität, 2023)
The photooxidative stability of a series of doubly bridged anthracenes was evaluated after their preparation via twofold macrocyclization of a bis(resorcinyl)anthracene. Lightfastness correlates with the energy levels of the highest occupied molecular orbital (HOMO), resulting in superior stability of the tetraesters compared to the tetraethers. The lengths and steric demand of the linker only plays a minor role for the ester-based compounds, which can be prepared in reasonable yields and thus tested in proof-of-concept organic light-emitting diodes. Double ester-bridging allows deep blue electro-luminescence, highlighting the importance of the choice of the functional groups used for macrocyclization. (2023-11-02)